Didactic System of Development of Pedagogical Cooperation in Current Innovative Educational Conditions (On the Example of Higher Education and General Secondary Education) (Journal of Pedagogical Inventions and Practices, 2023)
The article discusses the didactic system of developing pedagogical cooperation of future vocational education teachers in the conditions of innovative education in higher and general secondary educational institutions. The article explains the need to acquire high-level knowledge and professional skills, to be able to analyze educational activities and the production process, to promote new non-standard ideas, to master methods, tools, and professional and scientific information that meet modern requirements.